Cyclotrimerisation of isocyanates catalysed by low-coordinate Mn(II) and Fe(II) m-terphenyl complexes - Sharpe, Helen R.; Geer, Ana M.; Williams, Huw E.L.; Blundell, Toby J.; Lewis, William; Blake, Alexander J.; Kays, Deborah L. (Royal Society of Chemistry, 2016)
Two- and three-coordinate m-terphenyl complexes of manganese and iron are efficient catalysts for the selective cyclotrimerisation of primary aliphatic isocyanates affording isocyanurates in short reaction times and under mild conditions.